Central Nervous System Aspergilloma in an Immunocompetent Patient: A Case Report - Hasanreza MOHAMMADI; Sohrab SADEGHI; Shokrollah ZANDI (Tehran University of Medical Sciences, 2015)
Intracranial aspergilloma is extremely rare. The diagnosis and treatment of invasive CNS aspergillosis is very difficult. Early diagnosis is important for a successful treatment. Here, we report a case of intracranial aspergilloma in an 11-year-old boy in 2013. Good outcome was achieved by treatment with a combination of neurosurgical resection and antifungal administration, which we suggest is a good quality management plan.